2015
DOI: 10.1002/zaac.201500547
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of Dinuclear Double‐stranded Copper(II) Helicates with 3‐Ethoxy‐2‐hydroxyphenyl Substituted Diimines. Synthesis, Molecular Structure, and Host‐guest Recognition of H2O

Abstract: Abstract. Reaction of equimolar amounts of Cu(OAc) 2 ·H 2 O and bis [4-(3-ethoxysalicylideneamino)2 ) in a 1:1 THF/MeOH mixture leads to the formation of structure-analogous Cu II helicates of the composition [{Cu 2 L 2 }(H 2 O) 2 }]·4H 2 O. The helicates form left-and right-handed hydrogen bonded strands using the bound water mole-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…33−40 The ligands with an extra O-donor (−OMe, OEt, or −OH) generate bis-tridentate ligands with two sets of NO 2 donors that can increase the nuclearity of the helicates. However, their reaction with divalent 3d cations does not increase the nuclearity and tends to give helical dinuclear complexes with the [M 2 II L 2 ] general formula like those reported for the ligands H 2 L5 with Cu II , 41 H 2 L2 with Co II and Zn II , 39 or H 2 L with Cu II , Zn II , or Co II , 42,43 in which the extra O-methoxo or O-ethoxo donor atoms remain uncoordinated. Very unusual dinuclear triple and quadruple-stranded helicates or mesocates have been reported in two cases employing H 2 L4 and Dy III or H 4 L6 and Ti IV .…”
Section: ■ Experimental Sectionmentioning
confidence: 71%
“…33−40 The ligands with an extra O-donor (−OMe, OEt, or −OH) generate bis-tridentate ligands with two sets of NO 2 donors that can increase the nuclearity of the helicates. However, their reaction with divalent 3d cations does not increase the nuclearity and tends to give helical dinuclear complexes with the [M 2 II L 2 ] general formula like those reported for the ligands H 2 L5 with Cu II , 41 H 2 L2 with Co II and Zn II , 39 or H 2 L with Cu II , Zn II , or Co II , 42,43 in which the extra O-methoxo or O-ethoxo donor atoms remain uncoordinated. Very unusual dinuclear triple and quadruple-stranded helicates or mesocates have been reported in two cases employing H 2 L4 and Dy III or H 4 L6 and Ti IV .…”
Section: ■ Experimental Sectionmentioning
confidence: 71%
“…It is also interesting to note that in contrast to the Cu(II) helicates with the structurally related methylene or sulfurdiphenylene bridged 3-ethoxy-2-hydroxyphenyl substituted diimines [13], the related helicate from H 2 L 3 having a long hexamethylene spacer cannot bind a water molecule. This is obviously caused by the closely folded structure of this Cu(II) helicate which prevents the preorganization of an outer O 4 coordination sphere.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have published two double-stranded Cu(II) helicates with methylene and sulfurdiphenylene bridged 3-ethoxy-2-hydroxyphenyl substituted diimines. These recognize and bind two water molecules in their peripheral O 4 cavities [13]. Here we report four further Cu(II) complexes with structure-related hexadentate (H 2 L 1 and H 2 L 3 ) and tetradentate diimine ligands (H 2 L 2 and H 2 L 4 ) having cyclohexylidene, cyclohexylidenemethylene, hexamethylene and dioxotriphenylene spacer units varying in size and flexibility (Scheme 1).…”
Section: Introductionmentioning
confidence: 90%
“…26,27 In the literature there is a large variety of examples of helicoidal architectures derived from ligands whose formation is favoured by the existence of weak non-covalent π–π or CH⋯π interactions. 28–31 Along this line, it was found that the existence of non-covalent CH⋯π interactions favoured the helicate-type structure, contrary to expectations, since increasing the distance between the linking domains of the ligand should favour the mesocate conformation. 32…”
Section: Introductionmentioning
confidence: 96%